2018
DOI: 10.1016/j.eururo.2017.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Gene Expression is Predictive for Metastatic Primary Prostate Cancer

Abstract: Our stroma-derived metastasis signature can predict the metastatic potential of early stage disease and will strengthen decisions regarding selection of active surveillance versus surgery and/or radiation therapy for prostate cancer patients. Furthermore, profiling of stroma cells should be more consistent than profiling of diverse cellular populations of heterogeneous tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 31 publications
5
54
0
Order By: Relevance
“…Our data expand beyond previous evidence suggesting the clinical significance of stroma in PCa. Our results of fibroblast‐rich stroma predicting poor survival in hormone‐naive PCa is in line with Mo et al who showed that high VIM gene expression predicts metastatic potential in primary PCa. Moreover, we show that fibroblast‐rich stroma associated with CRPC, an observation supported by Thalmann et al who showed that human cancer‐associated fibroblasts may confer castration resistance of LNCaP cell line in vivo, suggesting that fibroblasts may have an active role in the development of CRPC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data expand beyond previous evidence suggesting the clinical significance of stroma in PCa. Our results of fibroblast‐rich stroma predicting poor survival in hormone‐naive PCa is in line with Mo et al who showed that high VIM gene expression predicts metastatic potential in primary PCa. Moreover, we show that fibroblast‐rich stroma associated with CRPC, an observation supported by Thalmann et al who showed that human cancer‐associated fibroblasts may confer castration resistance of LNCaP cell line in vivo, suggesting that fibroblasts may have an active role in the development of CRPC.…”
Section: Discussionsupporting
confidence: 92%
“…Olumi et al described a dramatic tumor‐promoting effect of carcinoma‐associated fibroblasts in PCa, and tumor stroma has been shown to be associated with aggressive disease features and shorter time to biochemical recurrence using needle biopsy as well as prostatectomy samples . Moreover, stromal gene expression analysis in prostatectomy samples revealed signatures specific for metastatic potential of PCa …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluate performance of DGS against five competitor methods: (Cuzick et al, 2011), (Penney et al, 2011), (Erho et al, 2013), (Mo et al, 2017), and (Tyekucheva et al, 2017). Area Under the receiver operating characteristic Curve (AUC), with the Delong method (DeLong et al, 1988;Robin et al, 2011) for confidence interval calculation, was used to compare the genomic signature's ability to predict metastasis in five validation datasets.…”
Section: Clinical and Biological Evaluationmentioning
confidence: 99%
“…Erho et al (2013) identified a gene expression based signature to predict early metastasis following radical prostatectomy using a random forest. Moreover, it was recently demonstrated that gene expression signatures derived from the stroma or microenvironment of the primary tumor are predictive of the metastatic progression of PCa as well (Mo et al, 2017;Tyekucheva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%